PROFIL MINAT MEMBACA ANAK USIA 4 – 5 TAHUN (Studi Deskriptif Pada Anak Usia 4 – 5 Tahun di RA Muhammad Iqbal Kota Cimahi) - Shinta Mutiara; Agni Noorgianib (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
Interest in reading is one of the provisions for children to be successful in both academic and non-academic fields, it is appropriate that interest in reading should be grown from an early age. This study aims to perceive the profile in children’s reading interest at the aged 4-5 years and to analyze the background of the behavior in which reading interest appears. Qualitative descriptive method as used in this study, portraying the profile of interest in reading with the data collections process by observation and interview. 70% of children aged 4-5 years at RA Muhammad Iqbal show their enthusiasm in books, symbols, sounds of letters and songs. Children are enthusiastic to see various types of reading books, from picture story books, magazines, and reading practice books which are provided by the teacher in classroom corner. 50% of parents frequently show reading activities at home, invite children to tell the story from picture book. Teachers and parents become role models for children to imitate the liking of reading and to provide motivating environments for children to be interested in reading. Keywords: profile of reading interest, reading, 4-5 years old children.